Analisis Studi Kelayakan Bisnis UMKM Kimbab Makanan Brooh - Nurlia Eka Damayanti; Ailah Nur Fitriah; Dhanil Sabarno Jeferson; Doni Saputra; Mahwahdah Luviany; Muhammad Izwan; Silvana Ryda Marccela; Muhammad Rifai (Ebisnis Manajemen, 2023)
This business feasibility study aims to analyze the potential and feasibility of establishing a kimbab Mekanan Brooh business. The research method used is descriptive with data collection through observation, survey, and interview. The results of the analysis show that the kimbab market opportunity is quite large seen from the interest and purchasing power of consumers. The marketing strategy is focused on brand image building and menu innovation. Technically, the initial capital is Rp565,000 with a 1-month payback. The form of business entity is an individual business with 7 employees. Financial analysis shows that it is feasible to run with several factors. In conclusion, Mekanan Brooh's kimbab business is worth establishing because it has good prospects in terms of market, technical, management, and financial aspects.